The relationship between the medial longitudinal arch and lower back disability among vocational school dancer - Ni Putu Diyah Ayuningtiyas; Made Hendra Satria Nugraha; Anak Agung Gede Angga Puspa Negara; Ni Komang Ayu Juni Antari (Physical Therapy Journal of Indonesia, 2023)
Background: Gianyar is one of the districts in Bali, Indonesia, that still maintain customs and traditions in ceremonies and rituals carried out as an implementation of culture. To support these activities, the performing arts commonly presented are traditional dance. The various foot movements in traditional dance will undoubtedly be a problem if there is a deformity in the foot. There is a phenomenon where abnormalities in the shape of the arch of the foot can potentially cause lower back disability. Deformities in the arch of the foot can affect the gait cycle, leg length, and the arrangement of the pelvic bones, which can trigger lower back pain. Objective: The purpose of this study was to determine the relationship between the medial longitudinal arch and lower back disability in traditional dancer Methods: This study is an analytical observational study with a cross-sectional research design conducted in December-January 2023. The study subjects were 74 students from Vocational School 3 of Sukawati. Majoring in traditional dance, aged 15 to 18 years, with a non-probability sampling technique using purposive sampling. Results: The researchers conducted anamnesis and examination according to inclusion and exclusion criteria and then observed the presence of a flat foot by measuring the Clarke angle value. The analysis used was bivariate analysis with the Spearman correlation test. The bivariate analysis results showed a significant relationship (p=0.000) between the medial longitudinal arch and lower back disability in traditional dancers at Vocational School 3 of Sukawati, with a muscular correlation strength and negative correlation coefficient value of -0.705. Conclusion: There is a significant relationship between the medial longitudinal arch and lower back disability in traditional dancers at Vocational School 3 of Sukawati.